Eligibility for competitive sport medical certification of children with severe hemophilia: Italian observational study - Lassandro, Giuseppe; Pastore, Carmela; Amoruso, Anna; Palladino, Valentina; Accettura, Domenico; Buzzi, Andrea; Tafuri, Silvio; Gallone, Maria Filomena; Valente, Roberto; Trisciuzzi, Rodrigo; Cassone, Cristina; Giordano, Paola (Acta Biomedica Atenei Parmensis, 2022)
Background ad aim of workː the position of Italian law regarding participation of prophylactically treated hemophiliacs to organized sport trainings and competitions remains unclear and this study focuses on the eligibility of pediatric patients in particular. Methodsː 16 patients age 3 to 15 years old, with severe haemophilia and prophylaxis starting age of 20,2 ± 2,2 months were enrolled. Weight, height, body mass index (BMI) and joint status (Hemophilia Joint Health Score [HJHS] and Haemophilia Early Arthropathy Detection with UltraSound, HEAD-US score) of patients were evaluated at start (T0) and after 12 months (T12) of a HIITS sport activity program. Resultsː All patients qualified for Italian competitive sport medical certification. Their weight and height increased after 12 months, without an increase in BMI (T0= 17,2; T1= 18,7; p>0,05). HJHS score did not change significantly (T0: 1.6 ± 1; T1: 2.1 ± 1.3; p>0.05). All children were right-handed and atrophy for the muscles of the right elbow significantly decreased (no atrophy seen at T0 in 4 of 16 patients and at T1 in 8 of 16 patients; p=0.045). Conclusionsː Hemophilic children, prophylactically treated, are capable to be included in sport groups and physical activity programs.